Assessment of perioperative stress in colorectal cancer by use of in vitro cell models: a systematic review - Kirkegaard, Tove; Gögenur, Mikail; Gögenur, Ismail (PeerJ, 2017)
Background The perioperative period is important for patient outcome. Colorectal cancer surgery can lead to metastatic disease due to release of disseminated tumor cells and the induction of surgical stress response. To explore the overall effects on surgically-induced changes in serum composition, in vitro model systems are useful. Methods A systematic search in PubMed and EMBASE was performed to identify studies describing in vitro models used to investigate cancer cell growth/proliferation, cell migration, cell invasion and cell death of serum taken pre- and postoperatively from patients undergoing colorectal tumor resection. Results Two authors (MG and TK) independently reviewed 984 studies and identified five studies, which fulfilled the inclusion criteria. Disagreements were solved by discussion. All studies investigated cell proliferation and cell invasion, whereas three studies investigated cell migration, and only one study investigated cell death/apoptosis. One study investigated postoperative peritoneal infection due to anastomotic leak, one study investigated mode of anesthesia (general anesthesia with volatile or intravenous anesthetics), and one study investigated preoperative intervention with granulocyte macrophage colony stimulating factor (GMCSF). In all studies an increased proliferation, cell migration and invasion was demonstrated after surgery. Anesthetics with propofol and intervention with GMCSF significantly reduced postoperative cell proliferation, whereas peritoneal infection enhanced the invasive capability of tumor cells. Conclusion This study suggests that in vitro cell models are useful and reliable tools to explore the effect of surgery on colorectal cancer cell proliferation and metastatic ability. The models should therefore be considered as additional tests to investigate the effects of perioperative interventions.
Keywords: Proliferation; Colorectal cancer; Invasion; Migration; Surgery; In vitro models; Apoptosis